On the optical properties and mineralogy of the surfaces of Near-Earth Asteroids - Mohamed, Rafa (Libyan Journal of Science &Technology, 2022)
In this article, we review the literature for constraints on physical properties and mineral composition of near-Earth asteroids. We discuss spectroscopic and microscopic studies of optical and physical effects and the surface structure of NEAs. This topic is of great importance to guess the nature and origin of these objects, and may help understanding investigation of extra-terrestrial bodies and providing indirect valuations of hazard on Earth via cosmic-ray bombardment, meteoroid, asteroid and comet impacts.